Integration of ICT in Flipped Classroom Physics Learning: Systematic Review - Wawan Wawan; Sudarmin Sudarmin; Woro Sumarni; Sunyoto Eko Nugroho; Adi Nur Cahyono; Arif Widiyatmoko (Universitas Negeri Semarang, 2023)
The integration of technology in classroom learning has become a common trend among educators. The use of technology in LMS, video conferencing, and others that are integrated with the learning process is very important. This review aims to analyze the integration of models and learning media in a flipped classroom for learning physics. The method used is a systematic review. The data was collected on an academic database, namely Scopus with the help of the Harzing's Publish or Perish application using the keyword “Flipped”. The analysis sample used is articles about learning Flipped Classroom as many as 1614 articles published in 2011-2021. Based on the six inclusion criteria, the articles analyzed were 20 articles. The instrument used is a coding sheet that summarizes the data and information of the article. The results show that the flipped classroom can use various media, in the form of videos, quizzes, LMS, online textbooks, blogs, discussion groups, Facebook groups, quizzes, LMS, PDF materials, PPT materials, Phet simulation, or in web form. The most commonly used media are videos, quizzes and LMS. In general, the use of media in flipped classrooms has been effective, but there are things that need to be considered in making media, including: 1) Making videos with shorter durations, 2) showing more video examples, 3) videos linked to the YouTube platform are good in LMS or independently, 4) Requires class guidance and agreement so that the use of media is effective.